JcTI-I: a novel trypsin inhibitor from Jatropha curcas seed cake with potential for bacterial infection treatment - Costa, Helen Paula S.; Oliveira, Jose Tadeu A.; Sousa, Daniele O.; Morais, Janne Keila S.; Moreno, Frederico B.; Monteiro-Moreira, Ana Cristina O.; Viegas, Ricardo A.; Vasconcelos, Ilka M. (Frontiers in Microbiology, 2014)
Jatropha curcas seed cake is a low-value by-product resulting from biodiesel production. The seed cake is highly toxic, but it has great potential for biotechnology applications as it is a repository of biomolecules that could be important in agriculture, medicine and industry. To explore this potential, a novel trypsin inhibitor called JcTI-I was purified by fractionation of the crude extract with trichloroacetic acid (2.5%, v/v) followed by affinity chromatography (Trypsin-Sepharose 4B) and molecular exclusion (Sephacryl S-200). Non-reducing SDS-PAGE and gel filtration showed that JcTI-I has approximately 20.0 kDa. Mass spectrometry analysis revealed that the intact molecular mass of JcTI-I is 10.252 kDa. Moreover, JcTI-I is a glycoprotein with 6.4% (m/m) carbohydrates, pI of 6.6, N-terminal sequence similarity around 60% to plant albumins and high stability to heat, pH and salinity. JcTI-I presented antibacterial activity against the human pathogenic bacteria Salmonella enterica subspecies enterica serovar choleraesuis and Staphylococcus aureus, with minimum inhibitory concentration (MIC) less than 5 µg/mL. Furthermore, JcTI-I did have inhibitory activity against the serine proteases from the tested bacteria. Otherwise, no hemolytic activity of human erythrocytes and signs of acute toxicity to mice were observed for JcTI-I. The results demonstrate the benefits of J. curcas seed cake as a source of trypsin inhibitor with potential for biotechnological application as a new antimicrobial agent against human pathogenic bacteria.